Coastal change rate, Mackenzie Delta to Tuktoyaktuk Peninsula, 1972 to 2000, Beaufort Sea, northern Canada - Sheila Hynes; Steve Solomon; Dustin Whalen (Polar Data Catalogue, 2016)
The Canadian Beaufort Sea coast is characterized by rapid rates of erosion and accretion forced by periodic storms, melting permafrost and long-term sea level rise. A re-examination of coastal change in the Beaufort Sea region was initiated by increased interest in exploration for hydrocarbon resources, as well as the observed effects of climate change on sea ice and coastal change. The resulting dataset provides a basis for the identification of hazard zones, the assessment of sediment budgets, and explaining the aspects of spatial variability in coastal responses in the region. Changes from 1972 to 2000 are dominated by retreat of the shoreline with average annual retreat rates of 0.6 m/a, but ranging as high as 22.5 m/a. Rates vary significantly both between and within zones of similar exposure, morphology and coastal geology with the highest average rates located in areas that are most exposed to northwest winds. In general, decadal-scale rates of change have remained constant during the 28 years encompassed by this study. The 1972, 1985 and 2000 shorelines were used as a basis for making measurements of coastal change during the 13 (1972-1985), 15 (1985-2000) and 28 (1972-2000) year periods which intervened. An automated procedure was developed to insert an orthogonal line between the two shorelines and the length of the line was inserted into a text file along with its bearing. The measurements were checked by an operator to determine whether erosion or accretion occurred (i.e. whether the change in position was negative or positive). Measurements of coastal change were made for the 1972-2000 and 1985-2000 intervals every 200 m and were assigned a geographic point coincident with the 2000 shoreline. The rate of retreat was calculated for each point by dividing the total amount of retreat by the number of years between each photo survey. For more information please refer to the datafiles entitled: CCIN12049_20160617_Mackenzie_Delta_retreat_rate_1972_2000_Extended_Metadata_FGDC.xml